Glass-Like Carbon Spheres — Activation, Porosity and Application Possibilities - Michio Inagaki; Chong-Rae Park; Jan M. Skowronski; Antoni W. Morawski (Adsorption Science & Technology)
A brief review on spherical carbons, including fullerenes and related spherical particles, is first provided, followed by a review of the results on air activation, porosity and applications focused on glass-like carbon spheres derived from phenolic resin spheres. Kinetic studies of the oxidation in air provide a fundamental understanding of activation process of glass-like carbon spheres. On the basis of the results, a new activation procedure, viz. two-step activation, is proposed, which provides ca. 10% higher oxidation yield in obtaining a comparative pore structure. Some possibilities for applications of these glass-like carbon spheres are also described, such as the adsorption/desorption of CO 2 gas and chlorinated methanes, the adsorption of organic molecules from their aqueous solutions, and the provision of electrodes for electric double layer capacitors and lithium ion rechargeable batteries.